Influence of multi-temperature primary air on the characteristics of MSW combustion in a moving grate incinerator. Issue 6 (December 2021) - Yan, Mi; Tian, Xinyi; Antoni,; Yu, Caimeng; Zhou, Zhihao; Hantoko, Dwi; Kanchanatip, Ekkachai; Khan, Muhammad Sajid
Abstract: Incineration is widely applied in municipal solid waste treatment and energy recovery, especially in China. The efficiency of energy recovery does not only depend on the design and construction of equipment, but it is also highly affected by the operation. Primary air temperature is a key parameter for incinerator operation, but there is still limited information about how primary air temperature affects MSW incineration. Fluid dynamic incinerator code (FLIC) and Fluent coupled model was used to study the influence of different primary air temperatures on MSW incineration in a moving grate incinerator with five zones of primary air feeding. Four different conditions were investigated and compared, namely, control case (20 °C for five grate zones), case 180 (180 °C for five grate zones), case I (190 °C for two front zones, and 180 °C for three behind zones) and case II (190 °C for two front zones, 170 °C for two middle zones, 160 °C for the last zone). The result demonstrated, as the air preheating temperature increased, so did the rate of moisture evaporation and volatile release, the latter of which could potentially lead to higher local maximum temperature in the furnace. It was possible, by using the different primary air temperature setup, to maintain a relatively high rate of moisture evaporation and total mass loss, while having a lower rate of volatile release. Ultimately, the multi-temperature primary air setup maintained a high time-average rate evaporation of moisture at 0.04230518 kg/m 2 s, and lowers the time-averaged rate of volatile release to 0.0396193 kg/m 2 s, thus, maintained the local maximum furnace temperature at 1685 °C. This concept can potentially be utilized in MSW incinerators to effectively evaporate moisture from MSW while keeping the local maximum temperature in the furnace to a reasonable temperature. Graphical Abstract: ga1 Highlights: Effect of primary air temperature on waste incinerators were analyzed by FLIC and CFD. Char conversion process effected by the release rate of volatiles. Multi-temperature primary air setup revealed the coolest peak bed temperature.